Democratic Parenting Policies in Building Responsibility Characters of Early Children - Emiliana, Widarti; Apriyanti, Nita (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to explore the role of democratic parenting in building the character of responsibility in 5-6-year-old children at Strada Kindergarten. Using a qualitative approach, the study involved parents who practiced democratic parenting and their children, as well as early childhood teachers, to gain an in-depth understanding of their experiences and interactions. Data were collected through in-depth interviews, behavioral observations, and questionnaires measuring parents' perceptions of parenting and children's character development. The results showed that democratic parenting, characterized by open communication, granting freedom with limits, and respecting children's opinions, contributed significantly to the development of children's responsible character. Children raised in this supportive environment tend to exhibit higher levels of responsibility, as they are taught to understand the consequences of their actions and are involved in decision-making. In addition, the study revealed that inconsistencies in parenting styles can affect the internalization of responsibility in children, making it important for parents and teachers to work together to create a stable and supportive environment. The study also highlighted the challenges faced in implementing democratic parenting, especially in the context of different cultures and family dynamics. As such, the findings provide valuable insights for parents and educators in their efforts to shape the character of early childhood responsibility, as well as emphasizing the importance of a balanced approach between freedom and guidance in parenting.